2010
DOI: 10.1523/jneurosci.6122-09.2010
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Potentials Modify the Transfer of Information at Photoreceptor Output Synapses in the Blowfly Compound Eye

Abstract: . The synapses are contained in compartments, lamina cartridges, whose extracellular potentials change with illumination (Shaw, 1984). We described these extracellular field potentials (FPs) using a novel permeabilization technique that converts neurons into extracellular recording probes. Having characterized extracellular FPs, we went on to study them using conventional microelectrodes. Extracellular space in a cartridge is electrically isolated from the body cavity and retina [input resistance (R in ) ϭ 6.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 52 publications
0
24
0
Order By: Relevance
“…In contrast, all hyperpolarizing responses decayed. Thus, it is possible that a mechanism that makes hyperpolarizing responses to increments transient, such as extracellular potentials within the lamina cartridge (Weckström and Laughlin, 2010), does not act similarly on depolarizing responses to decrements. Accordingly, only depolarizations require surround inputs for transience.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, all hyperpolarizing responses decayed. Thus, it is possible that a mechanism that makes hyperpolarizing responses to increments transient, such as extracellular potentials within the lamina cartridge (Weckström and Laughlin, 2010), does not act similarly on depolarizing responses to decrements. Accordingly, only depolarizations require surround inputs for transience.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, several mechanisms have been suggested to give rise to surround responses in bipolar cells, including pre-synaptic inhibition acting on photoreceptors, an ephatic effect, as well as proton modulation of neurotransmitter release (reviewed in Thoreson and Mangel, 2012). In LMCs both presynaptic inhibition and extracellular changes in electrical potential have been proposed to mediate spatial and temporal inhibition (Laughlin, 1974a; Shaw, 1975; Laughlin and Hardie, 1978; Hardie, 1987; Laughlin and Osorio, 1989; Juusola et al, 1995; Weckström and Laughlin, 2010). In L2 cells, we found that presynaptic inhibition acting on photoreceptors contributes to surround responses, and GABA A Rs further away from the photoreceptor-LMC synapse are also required (Figures 6, S6, 8 and S7).…”
Section: Discussionmentioning
confidence: 99%
“…This result was surprising, particularly since the visual response could be producing a field effect, with the visual response effects permeating through most of the brain (Fig. 4; Weckström and Laughlin 2010;Zimmerman 1978). Therefore, one would predict, based on the size of the optic lobes and the passage of current into the fly brain, that the central brain would produce similar changes in power as seen in the antennal lobes and optic lobes (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…5). Yet, the specificity of the changes in power at certain frequencies in the central brain indicated that there are localized circuit effects that are not just the result of spread of current through extracellular space (Weckström and Laughlin 2010;Zimmerman 1978). Instead, changes in power centrally could be due to Innovative Methodology local computations within the fly brain, such as synchronized, frequency-specific inputs from sensory regions in the fly brain or local neuromodulatory effects.…”
Section: Discussionmentioning
confidence: 99%
“…Signals were band-pass filtered (3 rd order butterworth filter, passband 0.5–200 Hz). Final noise levels were estimated as the difference between the averaged standard deviation of the intracellular and extracellular responses to the same blank stimulus32.…”
Section: Methodsmentioning
confidence: 99%